Analisis manajemen risiko perbankan syariah di era digital - Salsabila, Kika Andira (Maliki Interdisciplinary Journal, 2024)
The digitalization of sharia banking is progress that makes things easier for customers. In this digital era, marketing and service processes are carried out through online platforms so that this makes it easier to record transactions and services to customers. This development is also accompanied by greater market competition but with an increasingly wider market so that there is the possibility of gaining greater profits. However, digitalization also presents risks that may occur and cause losses. Therefore, there is a need for risk management which must be carried out in accordance with the form of risk that occurs.